LEVEL OF HEAVY METAL ACCUMULATION IN SOILS AND PLANTS WITHIN RESIDENTIAL DUMPSITES IN EZEAGU LOCAL GOVERNMENT AREA OF ENUGU STATE, NIGERIA - A.C, Okoro; L.C, Orakwe; CP, Nwachukwu; K.C, Ugwu (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2025)
Heavy metal accumulation in soils and plants poses serious environmental threat to people who live and engage into vegetable farming within these areas. This study aims at determining the accumulation of heavy metals in soil and Talinum triangulare at selected dumpsites at Ezeagu L.G.A of Enugu State. Soil samples were collected from four (4) locations, three dumpsites and a control site at 0-15cm and 16-30cm depths respectively. A total of twenty-four (24) soil samples were collected in triplicate, Six (6) from each of Iwollo-Oghe, Amansiodo and Akama-Oghe dumpsites and ESPOLY field (control). Each soil sample were collected using soil auger and were put in a labeled transparent polythene bag and transported to the laboratory for analytical procedure. Twenty-four plant (Talinum triangulare) samples were also collected from the four locations. The soils samples were analysed for their heavy metal content, physical and chemical properties while the plant samples were analysed for their heavy metal contents. The result of the soil analysis showed that heavy metal accumulation at 0-15cm soil depth had significant difference(p<0.05) for Boron and Zinc, but no significant difference(p<0.05) was observed in Iron(Fe) across the four treatment locations and that heavy metal accumulation at 16-30cm soil depth, significant difference(p<0.05) were observed in the heavy Metals-Iron(Fe), Boron(B) and Zinc(Zn) across the four treatment locations. Iron, Zinc and Boron values in the soil were found to be within the set critical concentration values. Zinc and Boron concentrations in Talinum triangulare were found to be higher above the set critical concentration values. It is recommended that vegetable crops should not be planted within dumpsites to avert food poisoning from heavy metals